The Strategic Role of Digital Innovation and Agility in Sustainable Organizations through Performance - Ayatulloh, Ayatulloh; Maliki, Budi Ilham; Komarudin, Mamay (Jurnal Economic Resource, 2025)
Bureaucratic transformation in the digital era requires public organizations to adopt innovation and digital agility to improve performance effectiveness and organizational sustainability. This study examines the impact of innovation and digital agility on employee performance and their implications for organizational sustainability, using the Cilegon City DPRD Secretariat as a case study. This study employed a quantitative approach with a survey method. Data were obtained from 93 employees of the Cilegon City DPRD Secretariat through a census questionnaire. Analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Construct validity was tested using factor loadings, while hypotheses were tested using t-statistics and p-values. The results show that innovation (t=5.293; p<0.05) and digital agility (t=3.649; p<0.05) significantly influence employee performance. Employee performance also mediates the relationship between the independent variables and organizational sustainability. The highest indicator of innovation is "the organization provides space for new ideas" (0.925), while digital agility is indicated by "quick adaptation to new technologies" (0.922). The findings demonstrate that innovation and digital agility are key pillars of an adaptive, productive, and sustainable bureaucracy. Innovation-based managerial strategies, digitalization of work processes, and strengthening organizational culture have been shown to improve individual and institutional performance. This research provides a strategic basis for the Cilegon City DPRD Secretariat to accelerate technology adoption, strengthen internal innovation, and build a sustainability-oriented performance evaluation system.